2000
DOI: 10.1002/(sici)1521-3773(20000403)39:7<1269::aid-anie1269>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

The Spatial Demand of Dendrimers: Deslipping of Rotaxanes

Abstract: The “dynamic spatial demand” of Fréchet‐type dendrons is compared with that of “conventional” building blocks by evaluation of the deslipping behavior of dendritic rotaxanes (see picture). This method leads to a ranking list of the size of voluminous building blocks, which will be useful for the rating of steric effects and the design and synthesis of new rotaxanes or less‐stable pseudorotaxanes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 1 publication
1
26
0
Order By: Relevance
“…280 The dendritic rotaxanes were prepared by Williamson ether coupling reaction between a bulky alkoxide and a dendritic bromide. Dethreading rates and computer modeling suggested that the steric requirements of the second generation dendron exceeded those of a trityl group, whereas the third generation appeared to be larger than the tert-butyl trityl group.…”
Section: Environmentally Responsive Cores: Dendritic Probesmentioning
confidence: 99%
“…280 The dendritic rotaxanes were prepared by Williamson ether coupling reaction between a bulky alkoxide and a dendritic bromide. Dethreading rates and computer modeling suggested that the steric requirements of the second generation dendron exceeded those of a trityl group, whereas the third generation appeared to be larger than the tert-butyl trityl group.…”
Section: Environmentally Responsive Cores: Dendritic Probesmentioning
confidence: 99%
“…In these cases the steric size of the stoppers is not the only parameter to have in mind. Subtle variations on the structure of the thread (flexibility, length, functional groups orientation) or macrocycle (void size) drastically effects on the energy necessary to break the mechanical bond. The paradigmatic example reported by Schalley nicely illustrates how a minimal hydrogen‐deuterium exchange at the stoppers can notably affect to the kinetic stabilization of interlocked species …”
Section: Introductionmentioning
confidence: 99%
“…Fréchet's dendrons had been employed as stoppers for the preparation of [36]. The spatial sizes of the various dendritic fragments were also determined by means of a deslipping experiment.…”
Section: Dendritic Oligoethers Based On a 35-dihydroxybenzyloxy Repementioning
confidence: 99%